'Grammatical laments, feminine arguments': Unconfessional inwardness in Webster's The White Devil. (April 2017) - Klotz, Lisa
In The White Devil Vittoria articulates her interiority, significantly in her dying confession, in which she verbalizes an inner state of moral blamelessness for the adultery she has committed and the murders she may have instigated. John Webster crafts a vague confession – a non-confession – that is unusual in relation to other contemporary plays and pamphlets based on actual murders; the full confession and repentance of the malefactor are conventional. Vittoria's non-confessional confession has the effect of denying Jacobean audiences any anticipated revelation and resolution in favour of a new 'realism' that perhaps proved too novel for Webster's dissatisfied audience.